Targeted delivery of LM22A-4 by cubosomes protects retinal ganglion cells in an experimental glaucoma model. (May 2021) - Ding, Yue; Chow, Seong H.; Chen, Jinying; Brun, Anton P. Le; Wu, Chun-Ming; Duff, Anthony P.; Wang, Yajun; Song, Jiangning; Wang, Jiang-Hui; Wong, Vickie H.Y.; Zhao, Da; Nishimura, Tomoharu; et al.
Abstract: Glaucoma, a major cause of irreversible blindness worldwide, is associated with elevated intraocular pressure (IOP) and progressive loss of retinal ganglion cells (RGCs) that undergo apoptosis. A mechanism for RGCs injury involves impairment of neurotrophic support and exogenous supply of neurotrophic factors has been shown to be beneficial. However, neurotrophic factors can have widespread effects on neuronal tissues, thus targeting neurotrophic support to injured neurons may be a better neuroprotective strategy. In this study, we have encapsulated LM22A-4, a small neurotrophic factor mimetic, into Annexin V-conjugated cubosomes (L4-ACs) for targeted delivery to injured RGCs in a model of acute IOP elevation, which is induced by acute IOP elevation. We have tested cubosomes formulations that encapsulate from 9% to 33% LM22A-4. Our data indicated that cubosomes encapsulating 9% and 17% LM22A-4 exhibited a mixture of Pn3m/Im3m cubic phase, whereas 23% and 33% showed a pure Im3m cubic phase. We found that 17% L4-ACs with Pn3m/Im3m symmetries showed better in-situ and in-vitro lipid membrane interactions than the 23% and 33% L4-ACs with Im3m symmetry. In vivo experiments showed that 17% L4-ACs targeted the posterior retina and the optic nerve head, which prevented RGCs loss and improved functional outcomes in a mouse model of acute IOP elevation. These results provide evidence that Annexin V-conjugated cubosomes-based LM22A-4 delivery may be a useful targeted approach to prevent the progression of RGCs loss in glaucoma. Statement of significance: Recent studies suggest that the therapy of effectively delivering neurotrophic factors to the injured retinal ganglion cells (RGCs) could promote the survival of RGCs in glaucoma. Our present work has for the first time used cubosomes as an active targeted delivery system and have successfully delivered a neuroprotective drug to the damaged RGCs in vivo . Our new cubosomal formulation can protect apoptotic cell death in vitro and in vivo, showing that cubosomes are a promising drug carrier system for ocular drug delivery and glaucoma treatment. We have further found that by controlling cubosomes in Pn3m phase we can facilitate delivery of neuroprotective drug through apoptotic membranes. This data, we believe, has important implications for future design and formulation of cubosomes for therapeutic applications. Graphical abstract: Image, graphical abstract